2018
DOI: 10.1186/s12940-018-0377-y
|View full text |Cite
|
Sign up to set email alerts
|

Does precautionary information about electromagnetic fields trigger nocebo responses? An experimental risk communication study

Abstract: BackgroundRegarding electromagnetic fields from mobile communication technologies, empirical studies have shown that precautionary information given to lay recipients increases their risk perceptions, i.e. the belief that electromagnetic fields are dangerous. Taking this finding one step further, the current study investigates whether precautionary information also leads to higher symptom perceptions in an alleged exposure situation. Building on existing research on nocebo responses to sham electromagnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Exposure perception to Wi-Fi related RF-EMF and risk perception were moderately correlated. This is consistent with previous research that reported the correlation between perceived exposure and risk perception to RF-EMF in general [6,11,12], as well as that from Wireless Local Area Networks (WLAN) [5].…”
Section: 253supporting
confidence: 92%
See 2 more Smart Citations
“…Exposure perception to Wi-Fi related RF-EMF and risk perception were moderately correlated. This is consistent with previous research that reported the correlation between perceived exposure and risk perception to RF-EMF in general [6,11,12], as well as that from Wireless Local Area Networks (WLAN) [5].…”
Section: 253supporting
confidence: 92%
“…Previous studies reported increased risk perception after the provision of precautionary information and selected media reports that strongly suggested the harmfulness of EMFs [ 5 , 26 , 28 ]. In contrast, we hypothesised that risk perception would be lower after receiving objectively measured personal RF-EMF exposure from Wi-Fi sources compared to the provision of precautionary or basic text information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The personality trait anxiety has already been investigated in the context of risk perception (e.g. Böhmert et al, 2017;Böhmert et al, 2018;Bouyer et al, 2001;Butler & Mathews, 1983;Witthöft & Rubin, 2013) "Anxiety is an emotional state defined by cognitive as well as somatic symptomatology such as feelings of tension, worried thoughts, increased blood pressure, sweating, derealization, and the anticipation of a future danger or threat" (Carlucci et al, 2018, p. 1). While (Freud, 1920) considered anxiety to be a unidimensional psychological state, current research differentiates between 'state anxiety' 6 and 'trait anxiety' 7 (Endler & Kocovski, 2001;Heeren et al, 2018;Laux & Spielberger, 1981;Spielberger, 1983).…”
Section: The Potential Of Narrative Visualizationsmentioning
confidence: 99%
“…Other studies also refer to risk perception, but the results were only obtained from questionnaire application without carrying out measurements of personal exposure [84][85][86][87][88][89][90][91], and other studies that measured exposure to RF-EMF did not evaluate risk perception [15,79,92,93]. As stated in the introduction, most studies on this topic are conducted in Europe, not in Mexico, and therefore this is a novel study.…”
mentioning
confidence: 99%